Local government website sustainability reporting: A mimicry perspective - Joseph, Corina; Taplin, Ross (Emerald Group Publishing Ltd, 2012)
Purpose – The purpose of this paper is to explain the role of mimetic isomorphism in relation to reporting sustainability information on local authority websites. Design/methodology/approach – The paper adopts a case study approach using semi-structured interviews of 16 Malaysian local councils. Findings – The paper finds that 15 out of 16 of the interviewed councils mimicked the sustainability information on websites of other councils. Interviews revealed that they do so to copy ideas about sustainability activities implementation rather than reporting format. Councils imitate both Malaysian and international websites. Practical implications – Websites play an important role in the improvement of sustainability development for learning, benchmarking and cost reduction. The pattern of copying websites suggests a hierarchical model where councils lower in the hierarchy copy councils at the next level in the hierarchy. Originality/value – This paper adds to the limited literature on mimetic isomorphism of public sector website sustainability reporting in developing countries.